2015
DOI: 10.4103/1596-3519.149910
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of injuries seen during an insurgency: A 5-year review of 1339 cases from Nigeria

Abstract: Injuries resulting from insurgency will continue to be a problem in many developing countries because their health facilities in terms of personnel and materials are ill prepared for such a situation .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Together, they serve as indicators of a population's health status with respect to a portfolio of health conditions and diseases. It is estimated that approximately 5-20 percent of combat-related casualties during the first ten years of OIF and OEF involved severe burns (Breederveld and Tuinebreijer, 2009;Wolf et al, 2006); this is consistent with a variety of estimates from other recent conflict settings, such as Mali (Akpoto et al, 2015), Nigeria (Amaefule et al, 2019;Dabkana et al, 2015), and Israel and Palestine (Mosleh et al, 2018).…”
Section: Incidence and Prevalence Of Burn Injuriessupporting
confidence: 74%
“…Together, they serve as indicators of a population's health status with respect to a portfolio of health conditions and diseases. It is estimated that approximately 5-20 percent of combat-related casualties during the first ten years of OIF and OEF involved severe burns (Breederveld and Tuinebreijer, 2009;Wolf et al, 2006); this is consistent with a variety of estimates from other recent conflict settings, such as Mali (Akpoto et al, 2015), Nigeria (Amaefule et al, 2019;Dabkana et al, 2015), and Israel and Palestine (Mosleh et al, 2018).…”
Section: Incidence and Prevalence Of Burn Injuriessupporting
confidence: 74%
“…Also, the effect has reduced the chances of Nigeria meeting the millennium and sustainable development goals as warned by [ 13 ]. Others include disruption of health activities [ 14 ], difficulty in tackling reported cases of tuberculosis [ 15 ] and increased occurrence of injury [ 16 ]. In recent times, the effects also include the adoption of school girls which might lead to raping and as a consequence, transmission of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Lessons from contemporary armed conflicts indicate gaps in prehospital care among civilians; a review of trauma patients from the 2014-16 Boko Haram insurgency concluded that very few patients had received any medical treatment prior to reaching hospital. 18 Similarly, studies from civilian hospitals in Iraq and Afghanistan demonstrated in-hospital mortalities under 1%, indicating a high burden of prehospital death. 19,20 No EMS service can be available everywhere and at all times; as such, teaching lay bystanders skills in managing a terrorism-related MCI prior to help arriving should be an essential component of civil preparedness efforts in any country, and F7M training may be an effective tool to build this capacity.…”
Section: Discussionmentioning
confidence: 99%